Gastrointestinal cytomegalovirus disease in renal transplant recipients: A case series - de Andrade, Luís G.M. [UNESP]; Rodrigues, Maria A.M. [UNESP]; Romeiro, Fernando Gomes [UNESP]; Carvalho, Maria F.C. [UNESP] (Wiley, 2012)
The purpose of this article was to report a series of 23 renal transplant recipients with histologically proven and immunohistochemically confirmed cytomegalovirus (CMV) lesions in the gastrointestinal tract (GIT) and to assess the risk factors associated with severe disease/mortality. CMV patients (n=23) were allocated into two groups: those who died (n=6) and those considered cured (n=17). Overall mortality rate was 26% (6/23). Initial symptoms suggestive of lower GIT involvement were observed in all death cases and in 35.3% of those cured (p=0.01). Enterorrhagia was seen in 83.3% of the patients who died. Death risk increased twofold (RR 2 [1.13-3.52], p=0.01) when symptoms of lower GIT involvement were initially observed and sixfold when enterrohagia was present (RR 6 [1.1-35.9], p=0.001). Among death cases, mean time at diagnosis was significantly more distant (2002±2.9×2008±1.6, p=0.04). The difference in mortality rates seen as service practices changed along the years demonstrates the importance of early diagnosis. © 2011 John Wiley & Sons A/S.
Keywords: Cytomegalovirus; Gastrointestinal; Renal transplantation; adult; cytomegalovirus infection; female; gastrointestinal infection; graft recipient; histopathology; human; human tissue; immunohistochemistry; intestinal bleeding; kidney transplantation; major clinical study; male; mortality; priority journal; risk assessment; symptom; Adult; Cytomegalovirus Infections; Female; Gastrointestinal Diseases; Humans; Immunocompromised Host; Kidney Transplantation; Male; Middle Aged; Opportunistic Infections; Risk Factors